The singular application of the modulor to the Oliveira do Hospital Pousada - Rodeia, Teresa Maria Ribeiro Belo, 1964- (2022)
The aim of this paper is to achieve a full understanding of the significance of the application of the Modulor, the system of proportions codified by Le Corbusier (1887-1965) that was published in 1950 (Le Corbusier, 1954), to the design for the Oliveira do Hospital Pousada, conceived by the architect Manuel Mendes Tainha (1922-2012). Manuel Tainha was born in Paço de Arcos, Portugal, having graduated in Architecture in 1950. He was one of the protagonists of the revision of the Modern Movement that characterised Portuguese architecture in the 1950. The pousada, located in the central interior of Portugal, designed between 1954 and 1960 and built between 1968 and 1972, remains a reference in the work of the architect and Portuguese architecture of the latter half of the 20th century.